Un aplicador manual de insecticidas granulados; su eficacia para el control de Spodoptera frugiperda (J.E. Smith) y Diatraea ap. con phoxim en el sorgo, Sorghum bicolor en el Salvador, C.A. - Reyes, R; Andrews, K.L; Chao Cheng, P; García, F.A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Late instar fall armywonn larvae, Spodoptera frugiperda, were effectively controlled in sorghum by application to the whorl of 0.04 to 0.07 g of phoxim which is a lower dosage than that currently recommended and used by farmers. control was unsatisfactory when the granules were applied only to those whorls which showed symptoms of recent attack. Application to all whorls resulted in satisfactory control of Diatraea spp. The use of a simple, inexpensive hand held bamboo aplicator prevented direct contact with the insecticide, and permitted rapid, precise and economical application of low dosages of the granules. Directions and illustrations for construction are given.